Neuregulin-1 converts reactive astrocytes toward oligodendrocyte lineage cells via upregulating the PI3K-AKT-mTOR pathway to repair spinal cord injury - Ding, Zhenfei; Dai, Ce; Zhong, Lin; Liu, Rui; Gao, Weilu; Zhang, Hui; Yin, Zongsheng (Biomedicine & pharmacotherapy, 2021)
[Display omitted] •TNF-α treatment induces dedifferentiation of primary rat spinal cord astrocytes.•Nrg1 converts reactive astrocytes toward oligodendrocyte lineage cells in vitro and in vivo.•Nrg1 upregulates PI3K-AKT-mTOR signaling pathway in astrocytes.•Nrg1 repairs SCI by enhancing remyelination, axonal preservation, locomotor recovery and inhibiting astrogliosis. Axonal demyelination is a consistent pathological characteristic of Spinal cord injury (SCI). Promoting differentiation of oligodendrocytes is of importance for remyelination. Conversion of reactive astrocytes with stem cell potential to oligodendrocytes is proposed as an innovative strategy for SCI repair. Neuregulin-1 (Nrg1) plays an essential role in the differentiation of oligodendrocytes. Therefore, it's a potential treatment for demyelination in SCI that using Nrg1 to drive reactive astrocytes toward oligodendrocyte lineage cells. In this study, tumor necrosis factor-α (TNF-α) was used to induce dedifferentiation of primary rat spinal cord astrocytes into reactive astrocytes and Nrg1 was used to induce astrocytes in vitro and in vivo. The results showed that astrocytes treated with TNF-α expressed immaturity markers CD44 and Musashi1 at mRNA and protein levels, indicating that TNF-α induced the stem cell state of astrocytes. Nrg1 induced reactive astrocytes to express oligodendrocyte markers PDGFR-α and O4 at mRNA and protein levels, indicating that Nrg1 directly converts reactive astrocytes toward oligodendrocyte lineage cells. Moreover, upregulation of PI3K-AKT-mTOR signaling activation in response to Nrg1 was observed. In rats with SCI, intrathecal treatment with Nrg1 converted reactive astrocytes to oligodendrocyte lineage cells, inhibited astrogliosis, promoted remyelination, protected axons and eventually improved BBB score. All the biological effects of Nrg1 were significantly reversed by the co-administration of Nrg1 and ErbB inhibitor, suggesting that Nrg1 functioned through the receptor ErbB. Our findings indicate that Nrg1 is sufficient to trans-differentiate reactive astrocytes to oligodendrocytes via the PI3K-AKT-mTOR signaling pathway and repair SCI. Delivery of Nrg1 for the remyelination processes could be a promising strategy for spinal cord repair.